2004
DOI: 10.1163/18759866-07303001
|View full text |Cite
|
Sign up to set email alerts
|

Carcinization in the Anomura – fact or fiction? II. Evidence from larval, megalopal and early juvenile morphology

Abstract: In this second of a two-part series, carcinization in the Anomura has been reviewed from early juvenile, megalopal, and larval perspectives. Data from megalopal and early juvenile development in ten genera of the Lithodidae have provided unequivocal evidence that earlier hypotheses regarding evolution of the king crab pleon were erroneous. A pattern of sundering, and decalcification has been traced from the megalopal stage through several early crabs stages in species of Lithodes and Paralomis, with supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
3
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 156 publications
0
28
3
3
Order By: Relevance
“…Recent studies on anomuran evolution have used molecular data [20,21,25,38], morphological (including developmental) data [41-43], or a combination of the two [19] to resolve phylogenetic relationships. These studies have dramatically increased our understanding of anomuran relationships and resulted in several major changes within higher-level classification [17,18,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on anomuran evolution have used molecular data [20,21,25,38], morphological (including developmental) data [41-43], or a combination of the two [19] to resolve phylogenetic relationships. These studies have dramatically increased our understanding of anomuran relationships and resulted in several major changes within higher-level classification [17,18,27].…”
Section: Discussionmentioning
confidence: 99%
“…They acknowledged that the crab-like form might have arisen multiple times across the Anomura, but in the case of pagurid/lithodid evolution they concluded that the opposite evolutionary trajectory was more plausible, i.e., the transition was from a “crab-like” body form to a ‘hermit-crab” body form through a series of habitat change, calcium loss, and consequential adult morphological adaptations. Subsequent studies showed that the linear evolutionary scenario proposed by Bouvier did not correspond to the ontogenetic changes that take place in the megalopa to juvenile crab stages in at least 10 species of eight lithodid genera [43,58]. Based on observations of the complex changes in pleonal tergites from megalopa to juvenile crab stages, these studies demonstrated that adult lithodid pleonal tergite structure in several species was the result of decalcification and sundering, not secondary calcification and fusion as had been proposed by Bouvier.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the extensive fusion of synaptic brain areas in C. maenas may be linked to the process of "carcinization", as was suggested for the fusion of the ventral ganglia to a ventral ganglionic mass in brachyurans (Stevcic 1971). The term "carcinization" was first introduced by Borradaile (1916), who hypothesized a multiple convergent transition from non-crab to crab-like body plans in decapod crustaceans (see reviews McLaughlin and Lemaitre 1997;McLaughlin et al 2004). Stevcic (1971), who synonymously used the term "brachyurization", suggested an increased coordination of movements and a more complex behavior mainly in amphibious and terrestrial crustaceans, as a result of the higher integrative properties of the condensed central nervous system.…”
Section: Deutocerebrum and Olfactory Pathwaymentioning
confidence: 99%
“…A particularly 'hot' topic has been the process of 'carcinisation', or the evolution of the 'crab' morphotype, respectively, the evolution of a crab-like habitus (e.g. McLaughlin and Lemaitre, 1997;McLaughlin et al, 2004;Hiller et al, 2010;Tsang et al, 2011;Scholtz, 2014). In evolutionary terms, any form of crab has evolved from an ancestral macruran or "lobster" morphotype.…”
Section: Introductionmentioning
confidence: 99%